2010
DOI: 10.1002/masy.201051021
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photostability and Red‐NIR Photosensitivity of Conjugated Polymer Charge‐Transfer Complexes

Abstract: Summary: A promising route to photostable and low-bandgap polymer materials for optoelectronic and photonic applications could be utilization of donor-acceptor ground-state charge-transfer complexes (CTCs) of wide-bandgap conjugated polymers. In this work, we report our results on photostability and photoelectric studies of CTC between an archetypical conjugated polymer MEH-PPV and low-molecularweight acceptor 2,4,7-trinitrofluorenone (TNF). By using the pump-probe laser photobleaching technique, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Incorporation of SE (5 wt %) resulted in a gradual decrease in band gap energies from 5.01 to 3.43 eV. The observed variation in E g with increasing SE content may be understood in terms of the formation of the stable charge transfer complexes (CTCs) between SE and PVA, which could inhibit the formation of other CTCs between the polymer and generated active oxygen species (leading to the initiation reaction of photodegradation of polymer). Therefore, it suggested that PVA/SE should show improved photostability. On the other hand, the intramolecular interactions between PVA and melanin at the molecular level were confirmed by the FTIR analyses in our previous report …”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of SE (5 wt %) resulted in a gradual decrease in band gap energies from 5.01 to 3.43 eV. The observed variation in E g with increasing SE content may be understood in terms of the formation of the stable charge transfer complexes (CTCs) between SE and PVA, which could inhibit the formation of other CTCs between the polymer and generated active oxygen species (leading to the initiation reaction of photodegradation of polymer). Therefore, it suggested that PVA/SE should show improved photostability. On the other hand, the intramolecular interactions between PVA and melanin at the molecular level were confirmed by the FTIR analyses in our previous report …”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23] Charge-transfer complexes (CTC) formed between the polymer donor and acceptor molecules in the electronic ground state have already been demonstrated to be an efficient way to tune the polymer chain conformation, [24][25][26][27] phase separation in blend films, [28,29] and photooxidation stability. [30,31] Paraschuk et al [32] revealed that the CTC is likely to form when blending a small amount of the acceptor 2,4,7-trinitrofluorenone with the amorphous donor polymer poly[methoxy-5-(20-ethylhexyloxy)-1,4-phenylenevinylene] (MEH-PPV). They pointed out that the formed CTC is highly dependent on the molecular skeletons of both the acceptor and donor polymer rather than the acceptor electron affinity and polymer concentration.…”
mentioning
confidence: 99%
“…As Figure shows, in the blend, this intragap feature disappears, and the SPV spectrum more or less follows the blend absorption. In fact, addition of TNF to MEH-PPV extends the blend absorption into the MEH-PPV optical gap as a result of CTC formation. , …”
mentioning
confidence: 99%